A developmental outlook on the role of cognition and emotions in youth volleyball and artistic gymnastics - Bisagno, Elisa; Cadamuro, Alessia; Rubichi, Sandro; Robazza, Claudio; Vitali, Francesca (Frontiers in Psychology, 2022)
Developmental and cognitive psychology recently started to take an interest in the sports domain, exploring the role of either cognitive functions or emotions in youth sport. However, to the extent that cognition and emotions are inextricably linked, studying them jointly from a developmental perspective could inform on their interplay in determining performance in different sports. This research examined the role of general cognitive abilities, attentional style, and emotions (controlling for age and experience), in predicting performance in youth volleyball and artistic gymnastics. A total of 218 female participants, of which 114 volleyball players and 104 artistic gymnasts (11 to 17 years old) were administered two measures of working memory and six measures of executive functions (namely inhibition, updating, and shifting). They also completed an attentional style and an emotion-related questionnaire. For each volleyball player, an individual performance index based on every gesture performed during the games and controlled for the team performance was computed. As a measure of gymnasts’ performance, scores in 2017-2018 competitions were used. Regression analysis showed that the main predictor of the volleyball players’ performance (R2 = .23) was a working memory-updating factor (ß = .45, p = .001), together with experience (ß = .29, p = .030) and high-arousal unpleasant emotions (ß = .30, p = .029), which positively predicted performance. Experience (ß = .30, p = .011), age (ß = -.36, p = .005) and high-arousal unpleasant emotions (ß = -.27, p = .030) were the predictors of gymnasts’ performance (R2 = .25). These results represent a first step in understanding if and how youth female athletes of open- and closed-skills sports rely on different psychological abilities. This line of research could offer insight to practitioners regarding which psychological abilities could be more relevant to train depending on the type of sport.